Composition of Some Apiaceae Seed Oils Includes Phytochemicals, and Mass Spectrometry of Fatty Acid 2‐Methoxyethyl Esters. Issue 5 (8th March 2019) - Knothe, Gerhard; Steidley, Kevin R.
Abstract : The seed oils of eight Apiaceae species, angelica ( Angelica archangelica ), anise ( Pimpinella anisum ), caraway ( Carum carvi ), carrot ( Daucus carota subsp. sativus), coriander (cilantro; Coriandrum sativum ), cumin ( Cuminum cyminum ), dill ( Anethum graveolens ), and parsley ( Petroselinum crispum ), obtained by hexane extraction, are investigated for their composition. As is known for the Apiaceae family, the major fatty acid in all oils is petroselinic acid (6( Z )‐octadecenoic acid). Quantification of petroselinic and oleic acids is carried out with their 2‐methoxyethyl esters, resolving the overlap occurring for methyl esters. Linoleic acid is the second most prominent fatty acid, followed by oleic acid with lesser amounts of linolenic, palmitic, and stearic acids. Most of these seed oils contain significant amounts of specific phytochemicals, including anethole in anise, carvone in caraway and dill as well as angelica in lesser amounts, cuminaldehyde in cumin, and apiole and myristicin observed only in parsley. Minor amounts of three C16:1 isomers, Δ4, Δ6, and Δ9, are observed in all oils, thus appearing characteristic of these seed oils. The mass spectra of 2‐methoxyethyl esters are reported with a salient feature being the base peak in the mass spectrum of 2‐methoxyethyl petroselinate at m / z 84 compared to the usual m / z 55. Practical Applications : Knowledge of the composition of seed oils is of utmost significance for their use in all applications, food and non‐food. Typically, these oils are obtained by hexane extraction of the seeds. This work now shows that seed oils from the common Apiaceae family, which includes many food‐related species, contain phytochemicals, which often have physiological significance and are usually associated with other plant parts. Besides this, the mass spectra of the 2‐methoxyethyl esters of fatty acids as found in these seed oils are reported as these esters were shown in the past to be especially suitable for quantification. This information is valuable for verifying the nature of these esters. The seed oils of Apiaceae species contain a variety of specific phytochemicals. The most common fatty acid is petroselinic acid, with 2‐methoxyethyl esters known to allow quantification of this acid. The mass spectra of fatty 2‐methoxyethyl esters are reported. Abstract : The seed oils of Apiaceae species contain a variety of specific phytochemicals. The most common fatty acid is petroselinic acid, with 2‐methoxyethyl esters known to allow quantification of this acid. The mass spectra of fatty 2‐methoxyethyl esters are reported.